2011
DOI: 10.3402/ijch.v70i2.17811
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of anemia among Inuit women in Nunavik, Canada

Abstract: Objectives. To assess the prevalence and main types of anemia present among non-pregnant Inuit women of Nunavik using a representative sample. Study design. A cross-sectional population-based study. Methods. Iron status was assessed in 466 women aged 18-74 who participated in the 2004 Nunavik Inuit Health Survey. The presence of different types of anemia has been evaluated based on available biochemical indicators of vitamins and of iron status. The correlation between iron status indicators, vitamin status pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0
4

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 24 publications
0
31
0
4
Order By: Relevance
“…Vitamin B 12 intake appeared adequate and is supported by observations of adequate serum B12 in Nunavik women. 15 Folate intakes were low but RBC folate levels, at least among young women, were not in a range associated with macrocytic anaemia. Given the current consumption of (fortified) wheat flour bread and other market foods, 16 severe folate deficiency would not be suspected.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin B 12 intake appeared adequate and is supported by observations of adequate serum B12 in Nunavik women. 15 Folate intakes were low but RBC folate levels, at least among young women, were not in a range associated with macrocytic anaemia. Given the current consumption of (fortified) wheat flour bread and other market foods, 16 severe folate deficiency would not be suspected.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, AOI was reported to explain 42% of the anaemia among post-menopausal Nunavik women in 2004, with 14% due to IDA and 44% remaining unexplained. 15 Iron intake and iron stores did not contribute to anaemia among older adults. Vitamin B 12 intake appeared adequate and is supported by observations of adequate serum B12 in Nunavik women.…”
Section: Discussionmentioning
confidence: 99%
“…This estimate is similar to the prevalence of iron depletion documented in a 2004 survey of women from Nunavik (30%). 30 In a study of 32 low-and middleincome countries, the mother's anaemia status was one of the most important predictors of anaemia in her children, surpassing socio-economic predictors in many countries. 31 It is likely that a similar relation exists for iron depletion in Inuit children.…”
Section: Discussionmentioning
confidence: 99%
“…The result of this study which revealed moderate anemia was the most common type of anemia in pregnant women, this is similar to result of other studies [1,16] and different with study done by Al.Shawi et al, (2012) who recorded high percent with mild anemia [6,12,17]. Severe anemia was seen in 20 cases it is in contrast to the study done by Geelhoed were no case of severe anemia was noted [18].…”
Section: Discussion:-mentioning
confidence: 96%